2006
DOI: 10.1007/s11418-006-0047-1
|View full text |Cite
|
Sign up to set email alerts
|

A new lignan from Aphanamixis polystachya

Abstract: A new lignan, polystachyol (1), two lignan glycosides, lyoniside (2) and nudiposide (3), and a sterol, ergosta-4,6,8(14),22-tetraen-3-one (4), with stigmasterol, and oleic and linoleic acids, have been isolated from an MeOH extract of the dried bark of Aphanamixis polystachya. The structures of the isolated compounds were elucidated by analysis of 1D and 2D NMR and mass spectroscopic data. The compounds did not have growth inhibitory activity against HeLa cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 6 publications
1
18
0
1
Order By: Relevance
“…Known compounds were identified as (4,4,14-trimethyl-3-oxo-24-nor-5α,13α,14β,17α,20S-chol-7-en-23-oic acid) (3), 16 hydroxydammarenone I (4), 17 ocotillone (5), 18 stigmasta-4-ene-3-one (6), 19 stigmasta-4,6,8(14),22-tetraen-3-one (7), 20 artelin (8), 21 polystachyol (9), 22 coniferyl alcohol (10), ferulic acid (11), 2,6-dimethoxyhydroquinone (12), antiarol (13), and 4-hydroxybenzaldehyde (14) by comparison with published literature data or direct identification by spectroscopic evidences. It was noted that compound 3 has been synthesized previously, 16 however, it was isolated from natural sources for the first time.…”
Section: Resultsmentioning
confidence: 99%
“…Known compounds were identified as (4,4,14-trimethyl-3-oxo-24-nor-5α,13α,14β,17α,20S-chol-7-en-23-oic acid) (3), 16 hydroxydammarenone I (4), 17 ocotillone (5), 18 stigmasta-4-ene-3-one (6), 19 stigmasta-4,6,8(14),22-tetraen-3-one (7), 20 artelin (8), 21 polystachyol (9), 22 coniferyl alcohol (10), ferulic acid (11), 2,6-dimethoxyhydroquinone (12), antiarol (13), and 4-hydroxybenzaldehyde (14) by comparison with published literature data or direct identification by spectroscopic evidences. It was noted that compound 3 has been synthesized previously, 16 however, it was isolated from natural sources for the first time.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, a variety of compounds have been obtained from the genus Aphanamixis, such as triterpenes, 3 limonoids, 4 lignans, 5 and alkaloids. 6 As our ongoing research for novel structural and significant bioactive natural products from the Meliaceae family, 7 three triterpenoids (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a 1˛,14ˇ-oxide bridge in both polystachin (10) 23 and dregeana-1 (2) was established by a NOESY correlation between H-1 and the C-19 methyl group. 2D NMR of 2 enabled the full assignment of 1 H and 13 C NMR resonances to be completed (Tables 1 and 2). …”
Section: Resultsmentioning
confidence: 99%
“…23 Detailed comparison of 1 H NMR data for 6 with that of limonoids 1, 5, 7, rohituka-9 (8), 24 and 12 suggested that 6 was identical to rohituka-5. 24 The absence of 13 C NMR data for rohituka-5 prompted us to undertake an unambiguous assignment of its NMR data, which was achieved by the application of 2D NMR techniques and are listed in Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation